"Mirror, Mirror on the wall / Who Is the Freest of Them All?": portrayals of Princesses in Grimms' Fairy Tales and Contemporary Children's Literature - Maria da Conceição Tomé; Glória Bastos (Red de Universidades Lectoras, 2013)
According to scholars, Grimm's Kinder- und Hausmärchen seems to have promoted patriarchal bourgeois values as part of the socialization process in the nineteenth century, modelling children's gender identity and behaviour over time. Taking into account, under the hegemonic representations of gender, that female identity becomes associated with a set of values and behaviours, we intend to analyse comparatively portrayals of Grimm's and contemporary Portuguese children's literature princesses. Our aim is to find out in what ways those princesses' images of the twenty-first century are substantially different from those conveyed by Grimm's fairy tales, analysing their emancipatory potential. Finally, we wish to apprehend which ideologies underpin those portrayals and to verify if they effectively lead to a new world vision by depicting women as real free human beings.